Needs Analysis: Academic Enhancement Psychoeducation Module Based on Guidance & Counselling Teachers and Subject Teachers’ Review - Nurul Fathihah Nor Azhar; Ahmad Jazimin Jusoh (International Journal of Education, Information Technology, and Others, 2022)
It is necessary to do a needs analysis to assure that the modules built will meet the requirements of the people who are going to employ them. This research was carried out with the intention of defining the requirements and prerequisites for the implementation of a module that is designed to aid secondary schools in the pursuit of academic progress. The questionnaire method was employed in this study, which is a quantitative approach. Moreover, the study sample was drawn at random from a population of 43 guidance and counselling teachers and 79 subject teachers from throughout Malaysia. The questionnaire covers five themes, namely: (i) general perceptions related to academic improvement programs; (ii) students’ level of awareness of academic importance; (iii) the need for programs or activities for the purpose of improving achievement; (iv) the effect of student involvement on academic programs or activities; and (v) the need for structured academic improvement programs or activity. Additionally, the researcher elicited subjective comments from respondents using open-ended questions. The findings may facilitate constructing the socioemotional module and, at the same time, identify the pertinent theory to be used as the milestone. This will be possible due to the findings’ ability to provide assistance.